Hotspot networks : - Minoli, Daniel (McGraw-Hill, 2003)
Need-to-Know Information on a Fast-Emerging technology from one of the top voices in networking -- that's what this detailed guide for network engineers and developers gives you. With Hotspot Networks, you can position yourself to promote, design, implement, or develop service applications in a hot new market. Book jacket.